2009
DOI: 10.1111/j.1464-410x.2009.09086.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fesoterodine and tolterodine extended release for the treatment of overactive bladder: a head‐to‐head placebo‐controlled trial

Abstract: voided volume per void (MVV); and the OAB questionnaire (OAB-q), Patient Perception of Bladder Condition (PPBC), and Urgency Perception Scale (UPS). Safety and tolerability were assessed and summarized over the 12-week study period. RESULTSFesoterodine (636 patients) significantly improved UUI episodes at week 12 (primary endpoint) compared with tolterodine ER (641 patients; P = 0.017) and placebo (313 patients; P < 0.001). Fesoterodine also produced significantly greater improvements than tolterodine ER in MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(102 citation statements)
references
References 26 publications
9
89
2
2
Order By: Relevance
“…The number of participants who required catheterization (n = 3, 0.8% vs n = 1, 0.3%) and the number who discontinued the study because of urinary retention (n = 4, 1.0% vs n = 1, 0.3%) were also higher with fesoterodine than placebo. The overall discontinuation rates in the fesoterodine (19.9%) and placebo (13.2%) groups in the present study were at the high end of the range of discontinuation rates observed in fesoterodine (10-21%) and placebo (9-15%) arms of trials conducted in younger participants; 18,19,34,35 discontinuation rates in the present study were slightly higher in participants older than 75 in both treatment groups.…”
Section: Discussionsupporting
confidence: 39%
“…The number of participants who required catheterization (n = 3, 0.8% vs n = 1, 0.3%) and the number who discontinued the study because of urinary retention (n = 4, 1.0% vs n = 1, 0.3%) were also higher with fesoterodine than placebo. The overall discontinuation rates in the fesoterodine (19.9%) and placebo (13.2%) groups in the present study were at the high end of the range of discontinuation rates observed in fesoterodine (10-21%) and placebo (9-15%) arms of trials conducted in younger participants; 18,19,34,35 discontinuation rates in the present study were slightly higher in participants older than 75 in both treatment groups.…”
Section: Discussionsupporting
confidence: 39%
“…In patients with pharmacogenomics variations in CYP2D6, the balance between toxicity and efficacy could be altered with tolterodine. Fesoterodine would not be affected by CYP2D6 polymorphisms [20]. Unfortunately, side effects are no less common with fesoterodine versus tolterodine, with dry mouth being the most commonly reported reason for discontinuation [17].…”
Section: • Favorable Cost-effectiveness Datamentioning
confidence: 99%
“…Herschorn et al 65 compared Fesoterodine and Tolterodine ER in a 12-week double-blind, double-dummy, placebo-controlled, randomized clinical trial that included 1,712 patients. Fesoterodine showed superior efficacy over Tolterodine ER 4 mg in reducing UUI episodes (primary endpoint), total and nocturnal voids, urgency episodes, severe urgency episodes, and frequency-urgency sum per 24 h, mean voided volume per void, except for nocturnal voids, and in improving most patient-reported outcome measures, except for the OABq sleep domain.…”
Section: Fesoterodinementioning
confidence: 99%